Factors Affecting The Effectiveness Of Integrated Management Services For Young Infant (MTBM) At Gadog Garut Health Center District West Java Province In 2020 - Syarifah Aini Hasibuan; Triana Indrayani; Cholisah Suralaga (Health Media, 2020)
Integrated Management of Young Infants (MTBM) aims to accelerate the reduction in child mortality, improve child health services, to find out whether children need to be referred or not, to provide the ability for families and communities to be able to carry out care at home. The achievement of MTBM at Gadog Health Center during the last three years has decreased and has not yet reached the expected target indicators.To determine the factors that affect the effectiveness of Integrated Management of Young Infant (MTBM) services at Gadog Health Center, Garut Regency, West Java Province in 2020. This research is an analytical survey with a cross sectional design. The research sample was 60 respondents. The sampling technique was carried out by total sampling. Data were collected using interviews and questionnaires. Data analysis used univariate and bivariate. The results of statistical tests showed that there was a significant relationship between completeness of facilities (p = 0.011), training (p = 0.003), competence (p = 0.027), motivation (p = 0.001) and the role of leadership (p = 0.035) with the effectiveness of Integrated Management services. Young Infants (MTBM) at Gadog Health Center, Garut Regency, West Java Province in 2020. The ineffectiveness of MTBM services at Gadog Health Center, Garut Regency is influenced by the completeness of facilities, training, competence, motivation and leadership roles